The Use Of Animated Videos to Increase Interest in Learning Islamic Religious Education Among Seventh Grade Students at Alam Banyuwangi Islamic School - Andrareza, Aqila Zhidan; Mahbubi, M. (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2026)
Islamic Religious Education (PAI) instruction in secondary schools often encounters challenges related to students’ low interest and limited understanding, particularly when dealing with abstract learning materials. This study aims to examine the effectiveness of animation-based instructional videos in improving students’ learning outcomes and engagement in PAI lessons. The research employed a Classroom Action Research design conducted in two cycles, involving 37 seventh-grade students at SMP ALAM Banyuwangi Islamic School. Data were collected through classroom observations, learning achievement tests, and documentation, and analyzed using descriptive quantitative and qualitative methods. The findings indicate a notable improvement in both teacher and student activities. Teacher activity increased from 70% in the initial cycle to 86.66% in the second cycle, while student activity rose from 63.33% to 86.66%. In terms of learning outcomes, the class average score improved from 73.33 in the pre-learning stage to 93.24 in the second cycle, with overall mastery reaching 89.19%. These results demonstrate that animation-based video media effectively facilitate students’ understanding of abstract concepts, enhance motivation, and encourage active participation in the learning process. This study highlights the importance of integrating audio-visual media into Islamic and religious education and contributes to the growing body of literature on digital media effectiveness in educational contexts. It is recommended that PAI teachers adopt animation-based videos as an innovative instructional strategy, while future studies may investigate their long-term impact on students’ affective and psychomotor domains